Mental health symptoms and disorders in Paralympic athletes: a narrative review - Swartz, L.; Hunt, K.; Bantjes, J.; Hainline, B.; Reardon, C. L. (British Journal of Sports Medicine, 2019)
Objectives: This narrative review summarises the literature on the mental health of Paralympic athletes, explores possible reasons for the paucity of research in this area and suggests directions for future research.